Ionotropic Receptor 76b Is Required for Gustatory Aversion to Excessive Na+ in Drosophila - Lee, Min Jung (Mol Cells, 2017)
Avoiding ingestion of excessively salty food is essential for cation homeostasis that underlies various physiological processes in organisms. The molecular and cellular basis of the aversive salt taste, however, remains elusive. Through a behavioral reverse genetic screening, we discover that feeding suppression by Na(+)-rich food requires Ionotropic Receptor 76b (Ir76b) in Drosophila labellar gustatory receptor neurons (GRNs). Concentrated sodium solutions with various anions caused feeding suppression dependent on Ir76b. Feeding aversion to caffeine and high concentrations of divalent cations and sorbitol was unimpaired in Ir76b-deficient animals, indicating sensory specificity of Ir76b-dependent Na(+) detection and the irrelevance of hyperosmolarity-driven mechanosensation to Ir76b-mediated feeding aversion. Ir76b-dependent Na(+)-sensing GRNs in both L− and s-bristles are required for repulsion as opposed to the previous report where the L-bristle GRNs direct only low-Na(+) attraction. Our work extends the physiological implications of Ir76b from low-Na(+) attraction to high-Na(+) aversion, prompting further investigation of the physiological mechanisms that modulate two competing components of Na(+)-evoked gustation coded in heterogeneous Ir76b-positive GRNs.